Development of earth card based on augmented reality materials relating to our earth to improve the adversity quotient of grade V students of state elementary school 1 Lorejo, Blitar District - ULIANA, RIZA; FATIH, MOHAMAD; OKTAVIANI, RAGIL TRI (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This research was motivated when fifth grade students, especially science students, were asked to solve problems, and they had difficulty finding solutions to the problems given. Their adversity quotient was relatively low. This research aims to develop augmented reality-based media with material related to our earth in order to increase intelligence in facing adversity. This research uses the Research and Development (R&D) method and the ADDIE development model. Data collected from media expert assessments was 92%, material expert assessments showed 98.3% (very valid), and practitioner experts gave an assessment of 94.54% (very feasible). Students' adversity quotient showed a figure of 0.64, which is included in the moderate criteria. The research results show that the process of developing augmented reality-based earth card media was carried out using the ADDIE development model including analysis, design, development, implementation, and evaluation. Assessments by experts show that the earth card media is very valid and very feasible to be used as a learning medium. Before the Earth Card media was implemented, the average student score was 4.15 and after the learning media was implemented, the average student score increased to 7.8.